The Pauline churches: a socio-historical study of institutionalization in the Pauline and Deutero-Pauline writings - MacDonald, Margaret Y. (Society for New Testament Studies monograph series, 1988)
The author studies the Pauline corpus in order to trace the process of institutionalisation in the Pauline communities. She claims that development can be traced since we have not only letters from Paul himself, but also the Pastoral epistles from the beginning of the second century, as well as Ephesians and Colossians, writings which are characteristic of the ambiguous period following the disappearance of the earliest authorities. This is the first substantial examination of the Pauline corpus from this angle; it also incorporates effectively insights from the social sciences.